Effect of unground oil palm ash as mixing ingredient towards properties of concrete - M. A., Sulaiman; Khairunisa, Muthusamy; Shariza, Mat Aris; M. H., Mohd Rasid; Paramasivam, R.; R., Othman (IOP Science, 2018)
Malaysia being one of the world largest palm oil producers generates palm oil fuel ash (POFA), a by-product in increasing quantity. This material which usually disposed as solid waste causes pollution to the environment. Success in converting this waste material into benefitting product would reduce amount of waste disposed and contributes towards cleaner environment. This research explores the potential of unground oil palm ash being used as partial sand replacement in normal concrete production. Experimental work has been conducted to determine the workability, compressive strength and flexural strength of concrete when unground oil palm ash is added as partial sand replacement. A total of five mixes containing various percentage of oil palm ash, which are 0%, 5%, 10%, 15% and 20% have been prepared. All specimens were water cured until the testing date. The slump test, compressive strength test and flexural strength test was conducted. The findings show that mix produced using 10% of palm oil fuel ash exhibit higher compressive strength and flexural strength as compared to control specimen. Utilization of unground oil palm ash as partial sand replacement would be able to reduce dependency of construction industry on natural sand supply and also as one of the solution to reuse palm oil industry waste.